Etika Bisnis Jual Beli Online Dalam Perspektif Islam: Tinjauan Pustaka - Anafih, Erwinda Sam; Harsono, Mugi (STIE AUB Surakarta, 2023)
Buying and Online selling is buying and selling activities online by utilizing internet technology. This form of marketing can be done by displaying the seller's product by uploading photos of the product so that communication between the seller and the buyer will be formed, but the buyer cannot see the desired item directly. Even though buying and sellingÂ online has various benefits, there are also problems that may arise, especially in uncertainty, namely whether the items in the photos match when they are received and the goods sent will actually be sent. Therefore, it requires a very high application of business ethics from online, namely a study that shows that trust in user acceptance of online buying and selling. So it is important to explore how to build trust in buying and selling online from an Islamic perspective. This research method is qualitative, using the field of literature review ( literature review ).Â The researcher collected data by gathering 14 selected relevant articles in the form of journals, books, and previous proceedings. The results of the literature review can be concluded that online buying and selling transactions in their application have tried to adapt to Islamic business ethics, but there is still some lack of understanding of good and correct online buying and selling business ethics according to an Islamic perspective. So it is necessary to have an understanding of business ethics from an Islamic perspective that includes ethical principles in a comprehensive manner.Â